Structuring of the periodization in antiquity: the Roman military training - Marques Junior, Nelson Kautzner (Tanjungpura Journal of Coaching Research, 2024)
Background and Study Aim. The sportive periodization originated from the military periodization of ancient civilizations and of the Greek Tetrad for the sportive preparation the ancient Greek athletes. The objective of the review was to explain the periodization of the Roman military training.  Materials and Methods. The articles were selected in January and February of 2024 in 10 databases (Google Scholar, PubMed, Research Gate, Scielo, Redalyc, Scopus, DOAJ, ScienceDirect, Semantic Scholar, and Latindex) with the following keywords: Roman military training, Roman soldiers, Roman Empire territory, Tetrad during Roman military training, Roman military equipment, and Roman military tactics.Results. Ancient Rome conquered almost all Western Europe, North Africa, and part of the Middle East because the nation was very militarized. The military training during ancient Rome for the soldiers and sailors had several types of training that were physical training, training, technical training, and technical and tactical training. So, for the war coach to organize all these training sessions for the Roman military, he needed to structure the periodization. The periodization of the Roman military training was used with several mesocycles of 4 to 6 months of duration during various moments of the year for the soldier and the sailor to always be prepared for war. In 146 B.C., the Roman Empire conquered ancient Greece and after this moment, the Romans used the scientific knowledge of the Greeks to structure the Roman military training. Then, the Romans used the Tetrad of the Greeks to structure the military training. Roman military training was structured with several Tetrad during 4 to 6 months. Therefore, the Tetrad was inserted into the mesocycle of 4 to 6 months.Conclusions. In conclusion, the periodization of the Roman military training was very organized for the military to achieve a high performance in the war.